2022
DOI: 10.1186/s12893-022-01480-8
|View full text |Cite
|
Sign up to set email alerts
|

Propensity-matched analysis of the efficacy of olanexidine gluconate versus chlorhexidine-alcohol as an antiseptic agent in thoracic esophagectomy

Abstract: Background In the present matched-cohort study, we investigated the efficacy of olanexidine gluconate in comparison with chlorhexidine-alcohol as an antiseptic agent in thoracic esophagectomy. Methods A total of 372 patients with esophageal cancer who were scheduled to undergo thoracic esophagectomy between 2016 and 2018 were assigned to one of two groups based on the preoperative antiseptic agent used in thoracic esophagectomy. We investigated the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 22 publications
0
6
1
Order By: Relevance
“…9 Fujita et al first reported a comparative study using propensity score matching analysis between 1.5% olanexidine and 1.0% chlorhexidine in thoracic esophagectomy; however, the study could not demonstrate any significant differences in SSI incidences. 10 This study could not demonstrate any significant decrease in 30-day SSI incidence; however, a significant reduction in organ/space SSI incidence was observed (p = 0.049).…”
Section: Discussioncontrasting
confidence: 72%
See 3 more Smart Citations
“…9 Fujita et al first reported a comparative study using propensity score matching analysis between 1.5% olanexidine and 1.0% chlorhexidine in thoracic esophagectomy; however, the study could not demonstrate any significant differences in SSI incidences. 10 This study could not demonstrate any significant decrease in 30-day SSI incidence; however, a significant reduction in organ/space SSI incidence was observed (p = 0.049).…”
Section: Discussioncontrasting
confidence: 72%
“…In contrast, two negative propensity score matching studies regarding olanexidine have been conducted; Kojima et al found no significant difference in SSI incidence in patients undergoing colorectal surgery compared with to 10% povidone‐iodine (8.6% vs. 8.6%, p = 1.000) 9 . Fujita et al first reported a comparative study using propensity score matching analysis between 1.5% olanexidine and 1.0% chlorhexidine in thoracic esophagectomy; however, the study could not demonstrate any significant differences in SSI incidences 10 . This study could not demonstrate any significant decrease in 30‐day SSI incidence; however, a significant reduction in organ/space SSI incidence was observed ( p = 0.049).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To our knowledge, except for a randomised trial by Obara and colleagues, 8 only non-randomised studies have been conducted on olanexidine. 67,68 Furthermore, the study by Obara and colleagues has an important methodological limitation. In the published protocol, an adjusted RR (ARR) with 95% CI was planned, but the final analysis was done by calculating an ARR with 90% CI.…”
Section: Discussionmentioning
confidence: 99%